REVIEW OF ISLAMIC LAW ON THE PRACTICE OF BUYING AND SELLING SAND IN SAMBAS WITH THE CONCEPT OF TAWAZUN - Muhtador; Hatoli; Nilhakim (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
Buying and selling sand is one of the businesses that is currently loved by the community. Sand has uses as a building material. Therefore, buying and selling sand must be considered from various aspects. Such as quality and quantity. Good sand quality makes buildings that have been designed can be built properly. Residential buildings are a primary need. In this context, before making a sale. There are sales methods that usually occur in the general public. Every buying and selling transaction has the option to be kept confidential or reported to one party if there are irregularities at the time of the transaction. The most important rule of buying and selling is tawazun or balance, which states that buying and selling should be done in a way that is oriented towards the world and the hereafter. Production must be coordinated with consumption and distribution. The focus of the problem in this study is: How is the practice of buying and selling sand with the concept of tawazun in Kartiasa Village, Sambas District, Sambas Regency? How is the review of Islamic Law on the practice of buying and selling sand with the concept of tawazun in Kartiasa Village, Sambas District, Sambas Regency. This research uses field research methods, namely research in the field aims to obtain information and describe events that occur in the field in accordance with the facts found in the field. While the approach that researchers use is qualitative descriptive. Based on the results of the research and discussion above, the following common thread is drawn: The practice of buying and selling river sand is carried out directly and indirectly using mobile communication devices, The reduction in the quantity of sand in one tailgate is done by collectors only for profit and this is seen as something that is contrary to the Qur'an resulting in illegal buying and selling because there is no clarity between price and dosage. Price fixing shows a mismatch between the amount of material received and the price paid, because the goods received by buyers are reduced. The review of Islamic Law on the practice of buying and selling sand with the concept of tawazun in Kartiasa Village, Sambas District, Sambas Regency has not fully complied with the provisions of Islamic law contained in one of the requirements of objects that Being an object of buying and selling is seen in terms of standard sizes and measurements. From this action, the element of reduction in the transaction of buying sand can cause tyranny for one party. Transactions that contain this dose reduction result in one of the conditions of the contract pillar not being fulfilled perfectly.